Are belief‐based justifications associated with metalinguistic awareness? A cross‐sectional study in school‐age children. Issue 1 (4th July 2017) - Spataro, Pietro; Rossi‐Arnaud, Clelia; Longobardi, Emiddia
Abstract: Previous research has consistently demonstrated that false‐belief (FB) understanding correlates with and predicts metalinguistic ability in preschoolers. Surprisingly, however, there is scant evidence on the question of whether this relation persists at later ages. The present cross‐sectional study sought to fill this gap by examining the association between FB understanding, belief‐based justifications and metalinguistic awareness. A sample of 150 children primary‐school children between 8 and 11 years of age were administered a test of receptive language, a second‐order theory‐of‐mind task and a comprehensive metalinguistic battery. The results of correlational and regression analyses showed that explicit metalinguistic awareness (in particular, performance in the Ambiguity and Phonemic Segmentation subtests) was significantly predicted by children's belief‐based responses to the justification question in the theory of mind task but only for children with small receptive vocabularies; in contrast, FB understanding made no independent contribution (either alone or in interaction with other measures). These findings complement and advance existing data by showing that, in school‐age children, the association between the 2 domains involves more mature, verbally explicit levels of FB understanding and metalinguistic awareness. Highlights: We examined the relation between metalinguistic awareness and theory‐of‐mind in primary‐school children. Metalinguistic awareness was associated to belief‐based justifications, but only for children with small vocabulary. In school‐age children the ability to provide verbal justifications plays a key role in the relation between theory‐of‐mind and metalinguistic awareness.